The boundaries of urban health policy: local powers, cholera morbus and social dynamics in Sicily in 1837. The projects of the strange “reorder” of the Civita District in Catania - Giannantonio Scaglione (Revista Movimentos Sociais e Dinâmicas Espaciais)
The aim of this paper is to highlight the historical events of a city of the Kingdom of the Two Sicilies in the first decades of the nineteenth century, facing the realisation of some urban interventions aimed at improving the conditions of public health within a district with health risk. The case study we have taken into consideration is the political conflict arisen between the municipal government of Catania and the Intendenza on the approval of health projects to restore the conditions of the “unhealthy” Civita district in front of the emergency of cholera in 1837. In this context, before the management of the financing of the project, the local city planning and provincial powers started a complicated contrast subverting the type of the project ending with the approval of some interventions that look more like works of urban rather than health reorganisation. In this sense, this research will focus on how the conflicts and tensions created by the city administration definitely hindered the real health emergency and the safeguarding of the population of the district.